Low bone volume - a risk factor for coronary calcifications in hemodialysis patients - Adragao, T.; Herberth, J.; Monier-Faugere, M.-C.; Branscum, A. J.; Ferreira, A.; Frazao, J. M.; Curto, J. D.; Malluche, H. H. (Clinical Journal of the American Society of Nephrology, 2009)
Background and objectives: There is increasing evidence that altered bone metabolism is associated with cardiovascular calcifications in patients with stage 5 chronic kidney disease on hemodialysis (HD). This study was conducted to evaluate the association between bone volume, turnover, and coronary calcifications in HD patients. Design, setting, participants, & measurements: In a cross-sectional study, bone biopsies and multislice computed tomography were performed in 38 HD patients. Bone volume/total volume, activation frequency, and bone formation rate/bone surface were determined by histomorphometry and coronary calcifications were quantified by Agatston scores. Results: Prevalence of low bone turnover was 50% and of low bone volume was 16%. Among the studied traditional cardiovascular risk factors, only age was found to be associated with coronary calcifications. Lower bone volume was a significant risk factor for coronary calcifications during early years of HD, whereas this effect was not observed in patients with dialysis duration >6 yr. Histomorphometric parameters of bone turnover were not associated with coronary calcifications. Conclusions: Low bone volume is associated with increased coronary calcifications in patients on HD.